Unconventional monetary policy and bond market connectedness in the new normal - Umut Akovalı; Kamil Yılmaz (Koç University-TÜSIAD Economic Research Forum (ERF), 2021)
Since the global financial crisis, major central banks gradually switched to unconventional monetary policies (UMPs) as part of their efforts to directly influence the long-term interest rates. This study analyzes the impact of conventional/unconventional monetary policies on sovereign bond return spillovers across countries and maturities since February 2007. Following the Taper Tantrum of mid-2013 and the ECB's policy convergence to other major central banks in 2015, the long-term return connectedness across countries increased, overtaking the short-term connectedness and lowering the dispersion of connectedness measures across maturities. Over the same period, net connectedness from short- to long-term maturities weakens, while net connectedness from medium- to long-term maturities stays strong. Finally, panel regression results show that UMPs in the form of higher central bank asset ratios led to higher pairwise long-term return connectedness even when the control variables such as trade and portfolio investment flows and the distance between pairs of countries are included in regression analysis.
Keywords: F34; G15; C32; G23; 330; Unconventional monetary policy; quantitative easing; yield curve; vector autoregression; variance decomposition; elastic net